2011
DOI: 10.1590/s0103-90162011000100001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of sisal fiber-cement roofing tiles for rural constructions

Abstract: Roofing provides the main protection against direct solar radiation in animal housing. Appropriate thermal properties of roofing materials tend to improve the thermal comfort in the inner ambient. Nonasbestos fiber-cement roofing components reinforced with cellulose pulp from sisal (Agave sisalana) were produced by slurry and dewatering techniques, with an optional addition of polypropylene fibers. Nonasbestos tiles were evaluated and compared with commercially available asbestos-cement sheets and ceramic tile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
(10 reference statements)
0
7
0
5
Order By: Relevance
“…Natural fibers are biodegradable, renewable and widely available in Brazil. Their use as reinforcement of cement-based matrices has added advantages such as high toughness, post-cracking performance, resistance to impact (MELO FILHO, 2005) and thermal insulation (PADILHA et al, 2001;TONOLI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers are biodegradable, renewable and widely available in Brazil. Their use as reinforcement of cement-based matrices has added advantages such as high toughness, post-cracking performance, resistance to impact (MELO FILHO, 2005) and thermal insulation (PADILHA et al, 2001;TONOLI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Solar radiation that reaches the roof is reflected, absorbed or transmitted in quantities that vary according to material physical properties (MICHELS et al, 2008;TONOLI et al, 2011). Therefore, there were no convection or irradiation losses of the energy falling on tiles, so that being absorbed and heating them and, consequently, being transmitted to the attic (region between the tile and the lining).…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that blue raffia presented the best zootechnical performance, being the worst performance observed in white raffia. In this sense, the use of materials that exhibit a low absorption coefficient, low thermal conductivity and diffusivity, and higher thermal inertia is essential to reduce heat transfer inside a building (TONOLI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisadores e fabricantes têm buscado a utilização de fibras alternativas ao amianto (Tonoli et al, 2011). O uso de fibras vegetais pode mostrar-se como opção viável por se tratar de um material renovável e de baixo custo, quando comparadas às fibras sintéticas.…”
Section: Introductionunclassified